Allicin and hesperidin protect sperm production from environmental toxins in mice - Golsa Behnejad; Tohid Mohammadi; Ali Soleimanzadeh (Scientific Reports)
Abstract This study investigates the protective effects of Allicin (A), a bioactive compound from garlic, and Hesperidin (HSD), a citrus flavonoid, against reproductive damage induced by para-nonylphenol (p-NP), an environmental pollutant, in mice. Fifty 8- to 10-week-old NMRI mice were divided into five groups: a control group, a group exposed to p-NP, and three groups treated with p-NP plus either Allicin, Hesperidin, or both. Treatments lasted for 35 days. Researchers analyzed sperm count, viability, motility, DNA damage, and morphology, alongside testicular parenchyma markers like antioxidant capacity (TAC), superoxide dismutase (SOD), glutathione peroxidase (GPx), and malondialdehyde (MDA) levels. Hormone levels (testosterone, LH, and FSH), testicular histopathology, apoptosis-related gene expression, and fertility indices were also evaluated. Results showed that mice treated with Allicin, Hesperidin, or both had reduced abnormal sperm morphology and DNA damage, with improvements in sperm motility, viability, and membrane integrity compared to the p-NP group. Antioxidant enzyme activities (TAC, SOD, GPx) and hormone levels increased, while MDA levels decreased, indicating reduced oxidative stress. Furthermore, expression of pro-apoptotic genes Bax and caspase-3 declined, while anti-apoptotic Bcl-2 expression rose. Treated mice demonstrated higher fertility indices and hormone levels. These findings suggest Allicin and Hesperidin mitigate p-NP-induced testicular damage by enhancing antioxidant defenses and regulating cell death pathways.